Usability of Ventricular Assist Devices in Daily Experience: A Multicenter Study. Issue 9 (September 2014) - Schima, Heinrich; Schlöglhofer, Thomas; zu Dohna, Renata; Drews, Thorsten; Morshuis, Michiel; Roefe, Daniela; Schmitto, Jan D.; Strüber, Martin; Zimpfer, Daniel
Abstract In daily life, the safe, intuitive use of ventricular assist devices (VADs) and especially their peripheral components is not only a question of life quality, but also sometimes crucial for survival. To investigate the advantages and disadvantages of different systems and to get patient feedback on preferred features, a multicenter study was initiated. Based on previous single‐center studies, a questionnaire was developed to ascertain patients' experiences, difficulties with, and desires concerning use of the system. This questionnaire was provided both to ongoing patients and to new VAD patients after a minimum hospital discharge time of 6 weeks, at a regular checkup. Additionally, the patients completed a standardized questionnaire on life quality (Kansas City Cardiomyopathy Questionnaire). The centers that contributed to this study were Bad Oeynhausen, Berlin, Hannover, and Vienna. Three hundred fifty‐two completed questionnaires on eight different pump types were obtained. An important result is that 42% of those questioned dropped their controller bag at least once. Depending on the device, between 2 and 55% disconnected it unintentionally. Confidence in safe use of the system decreased significantly with age, from 80% at age 20–30 years to 33% at 70–80 years. In devices with an LCD display, 94% considered the readability sufficient. Ninety‐four percent considered the training adequate. Between 22 and 88% of the patients called the emergency telephone hotline, depending on the device, and 23–46% depending on the center. This first multicenter study on VAD usability reveals considerable differences among devices and centers. The comparative assessment aims to help optimize device design, patient management, and training.